Herbivory alters thermal responses of algae. (5th November 2019) - Tseng, Michelle; Yangel, Evgeniya; Zhou, Yi Lin
Abstract: The temperature-size rule (TSR) describes the widespread pattern in which organisms grown at higher temperatures mature at smaller adult sizes, or exhibit smaller cell sizes in the case of microbes. Although the TSR has been shown in a wide range of taxa, most TSR studies have been conducted in the absence of species interactions such as competitors, parasites or predators. Given that these interactions are ubiquitous in nature, here we examine how the presence of a live herbivore ( Daphnia pulex ) affects the response of a cosmopolitan green algae ( Scenedesmus obliquus ) to the thermal environment. In the absence of direct herbivory, algae exhibited the characteristic TSR, exhibiting smaller cells, and smaller colonies at higher temperatures. However, in the presence of Daphnia herbivory, we saw no evidence of the TSR. Rather, both cell and colony size were uniform across the three rearing temperatures. These results suggest that Daphnia consume larger-sized algae at cooler temperatures, and smaller-sized algae at higher temperatures. Overall this study demonstrates that species interactions such as herbivory can alter the response of primary producers to the thermal environment, and suggests that the TSR may be readily modified in the natural world, where predators, herbivores and competitors abound.